Time Course Transcriptomic Study Reveals the Gene Regulation During Liver Development and the Correlation With Abdominal Fat Weight in Chicken - Xing, Siyuan; Liu, Ranran; Zhao, Guiping; Groenen, Martien A. M.; Madsen, Ole; Liu, Lu; Zheng, Maiqing; Wang, Qiao; Wu, Zhou; Crooijmans, Richard P. M. A.; Wen, Jie (Frontiers in Genetics, 2021)
Background: Liver is the central metabolic organ of animals. In chicken, knowledge on the relationship between gene expression in the liver and fat deposition during development is still limited. A time-course transcriptomic study from the embryonic (day 12) to the egg-producing period (day 180 after hatch) was performed to profile slow-growing meat-type chicken liver gene expression and to investigate its correlation with abdominal fat deposition. Results: The transcriptome profiles showed a separation of the different developmental stages. In total, 13,096 genes were ubiquitously expressed at all the tested developmental stages. The analysis of differentially expressed genes between adjacent developmental stages showed that biosynthesis of unsaturated fatty acids pathway was enriched from Day 21 to Day 140 after hatch. The correlation between liver gene expression and the trait abdominal fat weight (AFW) was analysed by weighted gene co-expression network analysis. The genes MFGE8, HHLA1, CKAP2, and ACSBG2 were identified as hub genes in AFW positively correlated modules, which suggested important roles of these genes in the lipid metabolism in chicken liver. Conclusion: Our results provided a resource of developmental transcriptome profiles in chicken liver and suggested that the gene ACSBG2 among others can be used as a candidate gene for selecting low abdominal fat weight chickens.